EVALUATION OF IMPLEMENTATION OF CLOUD COMPUTING in PT. SUPRANUSA SINDATA - Andika Ramadhan (Jurnal Informatika, 2018)
THE RESEARCH OBJECTIVES in this thesis is as evaluation of the implementation of Cloud Computing which has been in implementation in PT. Supranusa Sindata in order to develop into better again. METHODS were used in this study include the collection of journals and books as reference or grounding in analyzing. Data obtained from questionnaires to 100 respondents. The data were analyzed using factor analysis method after continued using regression analysis and designed with the IT Balanced Scorecard method. RESULTS OBTAINED is a form factor that can be used by PT. Supranusa Sindata to evaluate the implementation of Cloud Computing, technique systems engineering factors of cloud computing, cloud computing system management, performance measurement system of cloud computing, cloud computing system effectiveness. CONCLUSION with the model that can be used to evaluate the implementation of cloud computing and the design of strategic performance measurement using IT Balanced Scorecard is expected to grow so will affect the company's business performance and increase employee knowledge.